Duration of symptoms caused by COVID-19 in patients discharged from tertiary hospitals in Ceará - Ribeiro de Castro Júnior, André; Freire Gomes, Ticiane; Socorro Martins, Maria Iara; de Paula Santos, Marcos Augusto; Paiva de Abreu, Leidy Dayane; Aragão de Paiva, Iohanna; Franco Moreira, Francisco Jadson (O Mundo da Saúde, 2022)
Despite advances in knowledge about COVID-19, little is known about the course of the disease and its long-term outcomes. Therefore, post-pandemic research has focused on the sequelae and complications caused by the Coronavirus. Thus, the objective was to investigate symptomatological remains and their duration of discharged patients hospitalized for COVID-19 from three regional hospitals in Ceará. This is a descriptive, analytical cross-sectional study with a quantitative approach carried out from August to October 2021 through telesurvey. The final sample consisted of 49 patients in the first wave of the pandemic and 153 in the second, totaling 202 participants. Data were tabulated in an Excel® spreadsheet and analyzed according to descriptive statistics. There is a prevalence of male patients, 31 (63.3%) in the first period investigated, and 86 (56.2%) in the second wave. In the investigation of physical symptoms, fatigue/tiredness stood out, identified in 23 (46.9%) and 69 (45.1%) individuals according to the wave, followed by a lack of appetite in 13 (26.5%) and (40.5%). Shortness of breath was highlighted in the second period among 39 (25.5%) individuals. Symptoms such as memory loss, cough, and chest pain appear to be the most lasting, and were prevalent for up to 4 months after hospital discharge. While in the 2nd wave chest pain was cited lasting up to 6 months. In this context, this study exposes the main symptoms reported, pointing to the imminent need for public strategies for monitoring and intervention services with these patients.